Hubungan Dukungan Keluarga dengan Kepatuhan Menjalani Hemodialisis pada Pasien Gagal Ginjal Kronik di Rumah Sakit PMI Bogor Tahun 2024 - Rifi Sahbannul Hakim; Solehudin Solehudin; Lannasari Lannasari (Jurnal Anestesi, 2025)
In patients with chronic kidney failure, family support is very important for someone to undergo treatment therapy, whether carried out directly or indirectly. The role of the family, whether father, mother, husband, wife or children, provides support to someone to make them feel strong in undergoing therapy. This type of research is quantitative research with correlational analytical methods and cross-sectional design. Based on the research results, the total sample in this study was 64 patients with chronic kidney failure undergoing hemodialysis at PMI Bogor Hospital. Respondents with good family support were 41 respondents (64.1%) and 23 respondents (35.9%) had less family support. Respondents who were compliant with hemodialysis were 54 respondents (84.4%) and 10 respondents (15.6%) were non-compliant with hemodialysis. Based on the Spearman correlation test, it was found that family support with hemodialysis compliance had a significance value of p > 0.1, meaning the H0 hypothesis was accepted and if the significance value was p < 0.1, it meant H0 was rejected. So it is concluded that H0 is accepted, which means it is concluded that there is no relationship between family support and compliance with hemodialysis in chronic kidney failure patients at PMI Bogor Hospital in 2024.